2014
DOI: 10.1016/j.virol.2014.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride inhibits the initiation of Coxsackievirus and poliovirus RNA replication by inhibiting VPg uridylylation

Abstract: The mechanism of amiloride inhibition of Coxsackievirus B3 (CVB3) and poliovirus type 1 (PV1) RNA replication was investigated using membrane-associated RNA replication complexes. Amiloride was shown to inhibit viral RNA replication and VPgpUpU synthesis. However, the drug had no effect on polymerase elongation activity during either (−) strand or (+) strand synthesis. These findings indicated that amiloride inhibited the initiation of RNA synthesis by inhibiting VPg uridylylation. In addition, in silico bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This finding was supported by structural studies of CVB3 in which 3D pol was cocrystalized with VPg and the peptide was found to be bound to the back of the thumb, again distant from the active site (59). One possible explanation of how VPg could be uridylylated at this site is that the nucleotidylylation reaction is carried out by a second molecule of 3D pol (59, 103, 151). Such a “trans” uridylylation mechanism was supported also from structural studies of the EV71 polymerase complexed with VPg, in which VPg bound at the bottom of the palm domain could not access the catalytic site (27).…”
Section: Initiation Of Protein-primed Picornavirus Rna Synthesismentioning
confidence: 99%
“…This finding was supported by structural studies of CVB3 in which 3D pol was cocrystalized with VPg and the peptide was found to be bound to the back of the thumb, again distant from the active site (59). One possible explanation of how VPg could be uridylylated at this site is that the nucleotidylylation reaction is carried out by a second molecule of 3D pol (59, 103, 151). Such a “trans” uridylylation mechanism was supported also from structural studies of the EV71 polymerase complexed with VPg, in which VPg bound at the bottom of the palm domain could not access the catalytic site (27).…”
Section: Initiation Of Protein-primed Picornavirus Rna Synthesismentioning
confidence: 99%
“…As CVB3-TD virion RNA was shown to have covalently attached VPg, despite the fact that not all TD genomes have uridine as the 5′ nucleotide [ 50 ], the question arose as to whether the CRE-2C, which functions in the uridylation of VPg (reviewed by Paul and Wimmer [ 49 ]), is required for the replication of the TD CVB genomes. An inhibitor of VPg binding to the viral 3D polymerase, amiloride, decreases the initiation of enterovirus genome replication of both strands [ 112 ], an observation that verifies the process of nucleotidylation of VPg as being a part of the RNA initiation process. It has been shown that the disruption of the CVB3 CRE-2C structure via 16 mutations in the stem and loop ( Figure 6 ; mutations that did not alter the 2C amino acid sequence) inhibited the production of a cytopathic virus in cell culture, and generated double-stranded RF, but not single-stranded viral RNA, when replicons containing these mutations were transfected in cell culture [ 113 ].…”
Section: A Cis-acting Replication Element (Cre-2c) Plays a Role In Lo...mentioning
confidence: 99%
“…Amiloride (a diuretic drug) and its more potent derivative 5-(N-ethyl-N-isopropyl) amiloride (EIPA, Fig. 14B) were shown to inhibit CVB3 RNA replication in cell culture [29]. They compete with incoming nucleoside triphosphates (NTPs) and Mg 2+ .…”
Section: Inhibitors Of Replicationmentioning
confidence: 99%